Presence of Helicobacter pylori in betel chewers and non betel chewers with and without oral cancers - Amarasingha Indranee; Meedin Fahra; Perera Naomal; Jayakumar Gnanapragasam; Fernando Neluka; Holton John (BMC, 2009)
Abstract Background Betel chewing has been shown to predispose to periodontal disease and oral cancer. Studies show that people with gum disease are more likely to test positive for Helicobacter pylori (H. pylori). It is not known if the lesions produced by betel quid and the resulting, chemical changes predispose to colonization by H. pylori. Further the role of this organism in oral cancer is not known. Our objective was to determine the presence of H. pylori in oral lesions of thirty oral cancer patients and to determine the presence of IgG antibodies to H. pylori in oral cancer patients who are betel chewers and non betel chewers, healthy betel chewers and healthy non-betel chewers and to compare the presence of H. pylori in these four groups. This case control study was conducted at the Cancer Institute Maharagama and the Department of Microbiology, Faculty of Medical Sciences, University of Sri Jayewardenepura. Methods One hundred and seventy three subjects, of whom fifty three were patients presenting with oral cancer to the Cancer Institute Maharagama, sixty healthy betel chewers and sixty healthy non-betel chewers from the Religious and Welfare Service Centre Maharagama were tested for H. pylori by serology. Thirty oral biopsies from oral cancer patients were cultured under microaerophilic condition to isolate H. pylori. The statistic used was Chi-square test. Results Of the fifty-three oral cancer patients, forty-four were betel chewers. Among the 53 oral cancer patients examined, ten of forty-four (10/44 = 22.7%) patients who are betel chewers and four of nine (4/9 = 44.4%) patients who are non-betel chewers were detected positive for IgG antibody against H. pylori. In the healthy group (betel chewers and non betel chewers) ten (16.7%) of the healthy betel chewers tested positive for H. pylori by serology. None of the healthy non-betel chewers tested positive for H. pylori Fourteen [26.4%] of oral cancer patients tested positive for H. pylori by serology, of which two were also culture positive (Only thirty samples were cultured). The presence of H. pylori in betel chewers (with or without cancer) compared to non-betel chewers was statistically significant. (Chi-square test p < 0.05) The use of tobacco and areca nut in betel chewers was significant with the presence of H. pylori (p < 0.05). Conclusion There is a significant higher proportion of H. pylori in betel chewers compared to non-betel chewers but not between oral cancer patients compared to patients without oral cancer. Hence Betel chewing may predispose to colonisation with H. pylori in the digestive tract through swallowing the quid or during betel chewing.